Flexible antipredator behavior in herbivorous mites through vertical migration in a plant - Magalhães, S.; Janssen, A.; Hanna, R.; Sabelis, M.W. (Springer, 2002)
When predation risk varies in space and time and with predator species, successful prey defence requires specific responses to each predator. In cassava fields in Africa, the herbivorous cassava green mite (Mononychellus tanajoa) is attacked by three predatory mite species that are segregated within the plant: the leaf-dwelling Typhlodromalus manihoti and Euseius fustis occur on the middle leaves, whereas the apex-inhabiting T. aripo migrates from the apex to the top leaves only during the night. We found that differential distributions of these predators allow prey to escape predation by vertical migration to other plant strata. We studied the role of odours in the underlying prey behaviour on predator-free plants placed downwind from plants with predators and prey or with prey only. Prey showed increased vertical migration in response to predator-related odours. Moreover, these responses were specific: when exposed to odours associated with T. manihoti, prey migrated upwards, irrespective of the plant stratum where they were placed. Odours associated with T. aripo triggered a flexible response: prey on the top leaves migrated downwards, whereas prey on the middle leaves migrated upwards. Odours associated with E. fustis, a low-risk predator, did not elicit vertical migration. Further experiments revealed that: (1) prey migrate up or down depending on the stratum where they are located, and (2) prey discrimination among predators is based upon the perception of predator species-specific body odours. Thus, at the scale of a single plant, odour-based enemy specification allows herbivorous mites to escape predation by vertical migration.